Science Lecture Innovation Using PjBLSTEM-ESD to Improve Students' Critical Thinking Skills and Sustainability Consciousness to Strengthen SDGs 4 - Berry Kurnia Vilmala; Ridwan, Irwan Muhammad; Salman; Zamista, Adelia Alfama; Rihan, Hanifah Ghina; Nandiani, Elsa Marfina (Universitas Negeri Semarang, 2025)
The purpose of this research is to develop and implement project-based teaching materials with a STEM-ESD approach. These materials use a water theme in Science courses to strengthen the achievement of Sustainable Development Goals (SDG) 4 by improving students' critical thinking skills and sustainability consciousness. This research uses a mixed-methods approach with an Embedded Experiment Model design. The research instrument was developed through a validation process by 10 experts and a trial on 62 science education students to ensure validity and reliability. Implementation was carried out on a sample of 28 students from one university in Indonesia. Data collection used expert validation sheets, student response questionnaires, critical thinking tests, and sustainability consciousness scales. Analysis was carried out using Fuzzy Delphi Methods, the Rasch Model, N-Gain, and t-tests. Validation results showed that the teaching materials were very feasible to use (average validity of 89%). Empirical tests showed significant increases in critical thinking skills (N-gain = 0.39, medium effect size) and sustainability consciousness (N-gain = 0.30, low effect size). These findings confirm that implementing the PjBLSTEM-ESD model effectively contextualizes science concepts with sustainable development issues. It significantly supports the achievement of SDG 4 through meaningful and transformative education.